Effectiveness of Rehabilitation Package Based on Executive Performance of Signs (Child Behavior in Class, Participation and Group Cooperation, Attitude towards Authorities) in Children with Attention Deficit / Hyperactivity Disorder: Pilot Randomized Cont - Khalil Ghasemi; Mohammad Bagher Kajbaf; Amir Ghamarani; Hajar Torkan (Vesnu Publications, 2020)
Introduction: Attention Deficit and Hyperactivity Disorder (ADHD) is caused by dysfunction of the central nervous system and may affect all activities by the individual. The aim of this study was to determine the effectiveness of rehabilitation package based on executive performance of signs (child behavior in class, participation and group cooperation, attitude towards authorities) children with ADHD.Materials and Methods: The research project was a randomized clinical trial with the control group. 30 children with ADHD were selected from primary schools that were referred to in Isfahan health centers and clinics using convenient sampling and were randomly assigned into experimental and control groups. The experimental group underwent training in 11 2-hour sessions with the intervention of Dawson and Guare training package (target behavior, goal setting according to behavior, goal setting steps, monitoring, process evaluation, and gradual elimination of monitoring). The control group did not receive any parallel treatment process during the study (with the agreement of the child and the parents). Child behavior in the classroom, group participation and cooperation, attitude towards power authorities were assessed by the Connor Attention Deficit Hyperactivity Disorder Questionnaire. Data were analyzed using Mixed Model ANOVA.Results: The results showed that Dawson and Guare educational package significantly improved the signs of ADHD including child behavior in the classroom, participation and group cooperation, and attitudes towards power authorities (P ≤ 0.001 for all variables).Conclusion: It seems that Dawson and Guare educational package may be effective in managing the signs of children suffering from ADHD like child behavior in the classroom, group participation and cooperation, and attitudes toward power authorities.